Rockfall mitigation using a new probabilistic technique in the Cavazzo lake area - COCCOLO, ALESSANDRO; ARTINI, ENRICO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2003)
A case history of rock slope engineering concerning design of control measures adopted to protect a down slope area from rockfall hazard is described below. The paper deals with the first practical application of design procedure RDBD (Rockfall Defensive Barrier Design), developed by the authors and based on a probabilistic approach both during rockfall simulation phase and during design phase regarding defensive works. The innovative aspect of the procedure consists in the undertaking of probabilistic parameters, the Safety Levels, as conditioning elements of the entire project development, opposed to the deterministic sizes which have been adopted till today in this geotechnical engineering field. As a result, a multiple defensive system has been developed step by step, ensuring the prefixed safety level on the analyzed risk area and avoiding any superfluous defenses or dangerous underassessment.